Chemo-radiotherapy in patients with locally advanced squamous cell carcinoma of the head and neck with or without Lapatinib – a non randomised comparison study to assess the tolerance and efficacy - T, Naveen; Kiran B, Ravi; KR, Raghunandan (International Journal of Medical Research and Review, 2016)
Purpose of the study: We intend to test the efficacy of and toxicity of addition of Lapatinib to the standard of care in locally advanced squamous cell carcinoma of the head and neck (LAHNSCC). Materials/Methods: Between 2010 and 2012, thirty patients with histologically proven non metastatic LAHNSCC who fulfilled the inclusion and exclusion criteria for the study, stratified by disease stage and location were allocated to receive CTRT with Lapatinib or CTRT, the study approved by the institution review board and ethics committee. Results: Complete response was seen in 66% vs. 60% in the two arms at 3 months of follow up and this translated to 88% and 80% at 6 months of follow up (p=NS). Mucositis was seen early in the Lapatinib arm at 2nd week compared to 3rd week in the CTRT arm (p=0.04). Skin reactions developed early in the Lapatinib arm and was seen at a higher grade (p=0.02), Diarrhea was seen early and at a higher grade in the Lapatinib arm (p=0.01). Hematological toxicity was not significant between the arms. Conclusion: This study shows that addition of Lapatinib to the standard CTRT of LAHNSCC is efficacious and tolerable with accepted toxicity. Receptor Tyrosine kinase inhibitor mediated toxicity comparable to studies at other cancer sites. Late toxicity and long term survival with this therapy warrants a prospective stratified randomized trial.